Water management strategies for climate change mitigation in the Hadejia-Nguru wetlands, Northern Nigeria - Usman A. Ibrahim; Salisu Dan’azumi; Ali Aldrees; Sani I. Abba; M. J. Chiroma; Hassan H. Bdliya (Applied Water Science)
Abstract The Hadejia-Nguru wetlands (HNWs) are a UNESCO-declared Ramsar Site due to its importance as a habitat for varieties of exotic flora and fauna of international importance. Climate change, coupled with a declining river flow caused by river regulation, due to the construction of the Tiga and Challawa Gorge Dams upstream, is known to have adverse effects on the environmental sustainability of the wetlands. This research aims to propose reservoir operation rules that could be adopted to restore the river flow into the HNWs. Hydro-meteorological data were collected, and preliminary tests were carried out on the data before analysis. Five downscaled Global Climate Model outputs of RCP 4.5 scenario were selected under three scenarios of increased precipitation-unchanged temperature, increased temperature-unchanged precipitation and increased precipitation-increased temperature. WEAP model was set up to allocate water under four reservoir operation rules. The model was evaluated, and very good performances were shown. Results from the simulation show that Alternative III yields the highest reliability of more than 97% for both the Tiga and Challawa Gorge dams in all three climate change scenarios. Thus, Alternative III which assigned lower priorities for reservoir filling than municipal, environmental and irrigation water demands from October to June and higher priorities for reservoir refilling from July to September so that it could attain as high a reservoir level as possible was selected as the best operation rule for the two reservoirs.